Multiple pesticide residue determination in major vegetables purchased from Gazipur district of Bangladesh - Tasnim, Nuzat; Millat, Md Nasrul; Sultana, Sadia; Rahman, S M Mizanur; Prodhan, Mohammad Dalower Hossain (Asian-Australasian Journal of Food Safety and Security, 2022)
The present study was initiated to detect and quantify pesticide residues in three selected major vegetables (hyacinth bean, cauliflower and yard long bean) collected from 5 local markets of Gazipur district of Bangladesh. The vegetable samples were prepared by Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction technique and analyzed by Gas Chromatography (GC) equipped with Flame Thermionic Detector (FTD). In this study, 45 vegetable samples were analyzed. Out of 15 samples of hyacinth bean, 2 samples (13% of the total samples) contained pesticide residues above MRL and the remaining samples did not contain any detectable pesticide residues. In the instance of cauliflower, 2 samples (13% of the total number of samples) contained pesticide residues above MRL, while the remaining samples had no detectable pesticide residues. Pesticide residues with levels exceeding MRL were found and measured in 3 samples (20% of the total number of samples) from 15 yard long bean samples. From remnant samples, no pesticide residue was detected. This study depicts the overall scenario of pesticide contamination in vegetables specially in hyacinth bean, cauliflower and yard long bean available in the local markets of Gazipur city, Bangladesh. As a result, it is important to intensify routine pesticide residue monitoring in commercially cultivated vegetables. Asian Australas. J. Food Saf. Secur. 2022, 6 (2), 57-64